36 Impact of atrial fibrillation termination on long term outcome in persistent atrial fibrillation patients undergoing ACQMAP guided ablation. (May 2019) - Pope, Michael; Shi, Rui; Taylor, Mark; Das, Moloy; Murray, Stephen; Wong, Tom; Betts, Timothy
Abstract : Introduction: An acute response to ablation (arrhythmia termination or cycle length prolongation) is often presented as evidence of the significance of non-pulmonary vein (PV) mechanisms for AF maintenance and is an attractive procedural end point. Objectives: To investigate whether acute AF termination with ablation predicts long-term freedom from arrhythmia recurrence. Methods: We conducted a retrospective analysis of 100 patients who have undergone AcQMap (Acutus Medical) guided catheter ablation for AF at 3 UK centres. Acute success was defined as a spontaneous conversion to sinus rhythm (SR) during the ablation procedure. Long-term success was defined as freedom from any documented arrhythmia after a 3-month blanking period. Results: Mean follow up was 11 ±4 months. Baseline characteristics were well matched between groups except that a higher proportion of those with acute success were in SR at baseline (n=11, 28%, vs. n=6, 10%, p=0.022). During follow up, 68% (27/40) of patients with acute termination were free of arrhythmia recurrence compared with 50% (30/60) of those who required DCCV, a non-statistically significant difference of 0.18, p = 0.083. Binomial logistic regression was performed to evaluate the combined effect of acute termination and baseline SR on long-term outcome. The logistic regression model was not statistically significant (χ2 = 3.857, p = 0.145). For those undergoing first time procedures (n=81) ablation to SR vs DCCV freedom from recurrent arrhythmia was 74% vs 51% (p=0.041). In those in AF at baseline (n=83) ablation to SR vs DCCV freedom from recurrent arrhythmia was 69% vs 56% (p=0.048). Conclusion: The relationship between acute ablation to SR and long-term outcome is unclear but may be important for certain subgroups. More work is needed to fully explore the significance of this endpoint. Conflict of Interest: None